Lung Postmortem Autopsy Revealing Extramedullary Involvement in Multiple Myeloma Causing Acute Respiratory Distress Syndrome. (6th August 2014) - Ravinet, Aurélie; Perbet, Sébastien; Guièze, Romain; Lemal, Richard; Guérin, Renaud; Gayraud, Guillaume; Aliane, Jugurtha; Tremblay, Aymeric; Pascal, Julien; Ledoux, Albane; Chaleteix, Carine; Dechelotte, Pierre; et al.
Abstract : Pulmonary involvement with multiple myeloma is rare. We report the case of a 61-year-old man with past medical history of chronic respiratory failure with emphysema, and a known multiple myeloma (Durie and Salmon stage III B and t(4;14) translocation). Six months after diagnosis and first line of treatment, he presented acute dyspnea with interstitial lung disease. Computed tomography showed severe bullous emphysema and diffuse, patchy, multifocal infiltrations bilaterally with nodular character, small bilateral pleural effusions, mediastinal lymphadenopathy, and a known lytic lesion of the 12th vertebra. He was treated with piperacillin-tazobactam, amikacin, oseltamivir, and methylprednisolone. Finally, outcome was unfavourable. Postmortem analysis revealed diffuse and nodular infracentimetric infiltration of the lung parenchyma by neoplastic plasma cells. Physicians should be aware that acute respiratory distress syndrome not responding to treatment of common causes could be a manifestation of the disease, even with negative BAL or biopsy and could be promptly treated with salvage therapy.